Application of Word Card Media to Improve Beginner Reading Skills in Grade II Students at SDN Juruan Daya 2 - Andayani Purnamasari; Agus Wahdian; Jamilah (Anjasmoro: Islamic Interdisciplinary Journal, 2026)
Beginning reading skills is a basic ability that must be mastered by elementary school students as a foundation in developing literacy skills. However, the results of observations in Class II of Sdn Juruan Daya 2 showed that students ' initial reading skills were still low, so improvement efforts were needed through the use of appropriate learning media. This study aims to improve students ' beginning reading skills through the application of Word Card media. The study used the method of classroom Action Research (PTK) with Kemmis and McTaggart models that were carried out in two cycles, including the stages of planning, implementation of action, observation, and reflection. The research subjects were 25 second grade students of Sdn Juruan Daya 2. The data collection technique used a test of beginning reading skills, teacher and student activity observation sheets, and documentation. Data were analyzed descriptively quantitative and qualitative. The results showed an increase in reading skills beginning in each cycle. The average value of students increased from 59.5 in the pre-cycle to 68.6 in the first cycle, then increased to 77.0 in the second cycle. The percentage of learning completeness also increased from 0% in pre-cycle to 52% in cycle I and reached 84% in Cycle II. In addition, the activity and motivation of students increased during the learning process. The results showed that the application of Word Card media is effective in improving the reading skills of beginning Grade II students of Sdn Juruan Daya 2. Therefore, word card media can be used as an alternative learning media that is able to create a more active learning process, interesting, and meaningful for elementary school students.